Effect of Communication Skill Training Based on Calgary-Cambridge Observation Model on Midwifery Students\' Communication Skills - Asieh.Sadat Baniaghil (Journal of Research Development in Nursing and Midwifery, 2020)
Background: Communication skills are of top priority for health care providerchr('39')s professional traits and communication is an essential part of the midwifery care. Many studies of midwifery and midwifery studentschr('39') communication skills are poor and average. This study aimed to evaluate the effects of communication skills training through the Calgary Cambridge model on communication skill among midwifery students. Methods: This randomized controlled field trial was conducted in 2018. Thirty midwifery students were recruited using conventional sampling method from Golestan University of Medical Sciences, Gorgan, Iran. Then subjects was assigned into two experimental and control groups by stratified random allocation method. Initially, their communication skill was assessed using Queendom scale. Participants in the experimental group received communication skills training based on Calgary-Cambridge model in four four-hour sessions held twice weekly. The control group did not receive any intervention. Communication skill in both control and experimental groups was re-assessed respectively four weeks after pretest. Data were analyzed using the Mann-Whitney U test, the independent-sample t test and the paired-sample test in SPSS-16 software. Results: The pretest mean scores of communication skill in the experimental and the control groups were respectively 122.43±9.40 and 122.29±7.81, with no significant between-group difference. At post-test, the mean score of communication skill in the experimental and the control groups was respectively 122±8.06 and 120±8.08 and the between-group difference was not significant (P=0.51). Conclusion: Communication skills training through Calgary-Cambridge model is not effective in significantly improving midwifery students’ communication skill. Therefore, to improve communication skills, this model is insufficient and may need to be modified, or it is necessary to add more intervention to this model.